Somnometabolic Syndrome Revisited - Sanjay Kalra; Saptarshi Bhattacharya; Navneet Agrawal; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
The term somnometabolic syndrome has been used to describe a condition where obstructive sleep apnoea coexists with one or more components of metabolic syndrome. We propose a wider definition, stating that somnometabolic syndrome refers to the multifaceted, bidirectional relationship between sleep and metabolic health, including vascular health. This also includes the association of sleep with psychological and neurocognitive function. Keywords: Adreno-somnic axis, autonomic hygiene, cardiovascular disease, diabetes, insomnia, obesity, obstructive sleep apnoea, sleep disorders